Analisis Tingkat Security Awareness-Personal Threat Terhadap Ancaman Phishing Dengan Metode Technology Threat Avoidance Theory (TTAT) - Daila Sari, Indah; Hariyadi, Dedy; Sahtyawan, Rama; Kusumaningtyas, Netania Indi (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Phishing is a sort of cybercrime that involves obtaining sensitive information through the use of email, SMS, or compromised websites. The effects of phishing are caused by factors in the Technology Threat Avoidance Theory. The single best way to stop phishing attacks is to increase awareness of the risk of them happening among users or end users (human firewall). To determine the next steps in raising user knowledge, it is necessary to measure cybersecurity awareness, particularly against phishing assaults. Identify a few significant cybersecurity awareness of FTTI University of Jenderal Achmad Yani students in Yogyakarta. The investigation in this case included a phishing test and also employed online observation using observers who were asked questions based on the Technology Threat Avoidance Theory (TTAT). Using the MANOVA analysis method, factors influencing cybersecurity awareness analysis is conducted. Based on the analysis and testing of phishing tests as well as online questionnaires from the sample population, it shows that the sample is at a poor level of awareness. While the analysis of cybersecurity influence factors using the MANOVA analysis method shows that the results of the sig.> 0.05 value so that h0 is rejected. Based on the results of the study, it was concluded that FTTI students were still vulnerable to phishing attacks. Factor analysis using the MANOVA method shows that the dependent factor affects the level of cybersecurity awareness of the respondents but there is no significant difference between the dependent factors.